(untitled) (Anclajes, 2024)
The emergence of gay pride politics in Argentina takes places in the 1960s and 1970s in the context of the tensions between medical and criminological discourses on homosexuality, which respectively proposed that homosexuality was an immorality that should be criminally punished or an illness that could be treated. The conclusion is that, faced with an increase in police violence, maricas, gay men and transgender people tactically appropriated medical discourses, identifying themselves as sick and allying with medical doctors in their attempts to decriminalize sexual inversion. Then, in the context of the climate of cultural modernization, they would use the pretensions of scientific objectivity of medicine to demand the de-pathologization of homosexuality, abandoning the discourse of victimization, narrating their experiences as joyful, and mobilizing their base through the category of pride. The paper is based on the historiographic analysis of an extensive corpus of mass-circulation press, political organizations’ material, medical treatises and first-person documents.